Determinação de modelo de deterioração dos pavimentos para a malha rodoviária do Estado do Ceará - Cunha, Carlos Roberto (2008)
Study careful planning in the medium and long term, should provide reliable information for decision-making, avoiding unnecessary costs to society due to poor maintenance of roads. For this, many institutions make use of road management tools, such as the Pavements Management Systems - PMS. These systems use models to predict pavement performance and identify the best solutions to be implemented, define the estimated costs, prioritize investments, according to scenarios of budget constraints imposed. This study aimed to determine a pavements deterioration model on the state highways in Ceará, using data from monitoring by the Ceará Department Buildings and Highways - DER, through the Continuous Visual Survey - CVS, conducted from 2001 to 2007, except 2003. With this series, and the database of the institution could establish a correlation between the pavement age versus the defects equivalent factor and the equivalent factor for defects in sequential years to crack fatigue and block, and patch the sinking. Were also established relations grouping the data by traffic levels and type of surface, which in some cases significantly improved the confidence of the model. It is hoped that this study will contribute to improving the quality of performance projections for highway pavements Ceará.